Fibro-osseous pseudotumor of the digit - Kumar, Sanjiv; Rai, Tushar; Singh, Sudhir; Verma, Reetu (International Journal of Research in Medical Sciences, 2017)
Fibro-osseous pseudotumor of the digitis a very rare benign lesion however it may be a cause of concern as it forms differential diagnosis to aggressive bone forming tumors like extraskeletal osteosarcoma. Till date only a few cases have been reported in the literature. We came across a case of 7yr old female presented with complains of post traumatic progressively growing hard swelling present on the palmar surface of the hand at the hypothenar region for last 6 months. Investigations i.e. X-rays, MRI and CT scan were done along with other blood investigations to rule out other common diseases such as exostosis or myositis ossificance or extraskeletal osteosarcoma. Excisional biopsy of the lesion confirmed the diagnosis of fibro-osseous pseudotumor of the digit.